Anisotropy in subduction zones: Insights from new source side S wave splitting measurements from India. Issue 8 (12th August 2017) - Roy, Sunil K.; Kumar, M. Ravi; Davuluri, Srinagesh
Abstract: This study presents 106 splitting and 40 null measurements of source side anisotropy in subduction zones, utilizing direct S waves registered at two stations sited on the Indian continent, which show null shear wave splitting measurements for S K S phases. Our results suggest that trench‐parallel anisotropy is dominant beneath the Philippines, Mariana, Izu‐Bonin, and edge of the Java slab, while plate motion‐parallel anisotropy is observed beneath the Solomon, Aegean, Japan, and Java slabs. Results from Kuril and Aleutian regions reveal trench‐oblique anisotropy. We chose to interpret these observations primarily in terms of mantle flow beneath a subduction zone. While the two‐dimensional (2‐D) slab entrained flow model offers a simple explanation for trench‐normal fast polarization azimuths (FPA), the trench‐parallel FPA can be reconciled by extension due to slab rollback. The model that invokes age of the subducting lithosphere can explain anisotropy in the subslab, derived from rays recorded at the updip stations. However, when downdip stations are used, contributions from the slab and supraslab need to be considered. In Japan, anisotropy in the subslab mantle shallower than 300 km might be associated with trench‐parallel mantle flow resulting in the alignment of FPA in the same direction. Anisotropy in the deeper part, above the transition zone, is probably associated with 2‐D flow resulting in trench‐normal FPA. Anisotropy in the Mariana Trench might be associated with trench‐parallel mantle flow in the supraslab region, with similar deformation in the upper mantle and the transition zone. Key Points: New measurements of subslab anisotropy from diverse subduction zones The 2‐D entrained and trench‐parallel extension explain trench‐normal and trench‐parallel anisotropy For shallow slabs age‐dependent model explains updip but not downdip anisotropy